2022
DOI: 10.3390/ani12141771
|View full text |Cite
|
Sign up to set email alerts
|

Milk Composition and Production Efficiency within Feed-To-Yield Systems on Commercial Dairy Farms in Northern Ireland

Abstract: This study examined the relationships between milk yield and diet composition, nutrient intakes, milk composition, and feed use efficiency when concentrates were offered using a feed-to-yield (FTY) approach. The study was conducted on 26 dairy farms in Northern Ireland. Cows (n = 3471) were fully housed and were offered concentrates on an FTY basis. Individual cow genetic information was obtained for 18 herds. Concentrate intakes of individual cows were either obtained from the farms or calculated, while milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Similarly, analogous data were obtained when TC spiked in raw milk was processed on PureCubeNHS beads functionalized with a-TC8 aptamer (TC/TC0 for the eluted fraction e2). Additionally, milk contains several compounds that could interfere with the aptamer–antibiotic binding [ 44 , 45 ], while this adverse effect is less present when the interaction of antibiotics is mediated by small molecules or even ions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, analogous data were obtained when TC spiked in raw milk was processed on PureCubeNHS beads functionalized with a-TC8 aptamer (TC/TC0 for the eluted fraction e2). Additionally, milk contains several compounds that could interfere with the aptamer–antibiotic binding [ 44 , 45 ], while this adverse effect is less present when the interaction of antibiotics is mediated by small molecules or even ions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The goat milk yield and composition according to goat breed and SCC group are presented in Table 2 . The present study showed that Saanen goats yielded ( p < 0.001) more milk (2.45 ± 0.04 vs. 1.71 ± 0.02 kg/day), but their milk was significantly lower in fat (3.13 ± 0.10 vs. 4.39 ± 0.13%) and protein (3.02 ± 0.04 vs. 3.53 ± 0.05%) content than that of Alpine goats [ 20 ]. Lower fat and protein content with higher milk yield in Saanen goats may be attributed to goat genetics and milk dilution effects [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that Saanen goats yielded ( p < 0.001) more milk (2.45 ± 0.04 vs. 1.71 ± 0.02 kg/day), but their milk was significantly lower in fat (3.13 ± 0.10 vs. 4.39 ± 0.13%) and protein (3.02 ± 0.04 vs. 3.53 ± 0.05%) content than that of Alpine goats [ 20 ]. Lower fat and protein content with higher milk yield in Saanen goats may be attributed to goat genetics and milk dilution effects [ 20 ]. A few previous studies revealed similar milking results: Saanen goats had significantly higher daily milk yields (2.15–2.63 kg/day) compared with Alpine goats (1.76–2.08 kg/day) [ 21 , 22 ], while milk composition varied differently between investigated breeds.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the strongest effect with 0.91 was identified for protein content. Craig et al [46] already showed that protein content is closely related to productivity. With increasing milk yield, the amount of protein decreases, explaining the opposite signs of the path coefficients of milk yield and protein content in our model [46].…”
Section: Manifest Variables On Intramammary Infection and Productionmentioning
confidence: 99%
“…Craig et al [46] already showed that protein content is closely related to productivity. With increasing milk yield, the amount of protein decreases, explaining the opposite signs of the path coefficients of milk yield and protein content in our model [46]. Regarding udder health, protein content reacted very sensitively, especially to somatic cell count alterations, while fat content was more stable [9].…”
Section: Manifest Variables On Intramammary Infection and Productionmentioning
confidence: 99%